Allogeneic mesenchymal stromal cell therapy in kidney transplantation: should repeated human leukocyte antigen mismatches be avoided? - Bezstarosti, Suzanne; Erpicum, Pauline; Maggipinto, Gianni; Dreyer, Geertje J.; Reinders, Marlies E. J.; Meziyerh, Soufian; Roelen, Dave L.; De Fijter, Johan W.; Kers, Jesper; Weekers, Laurent; Beguin, Yves; Jouret, François; et al. (Frontiers in Genetics, 2024)
Mesenchymal stromal cells (MSC) have immunomodulatory properties and are therefore a promising tool in kidney transplantation. While most studies have been conducted with autologous MSC, using allogeneic MSC as an off-the-shelve product is more feasible in clinical settings. However, allogeneic MSC could potentially induce an immune response, which might eventually be directed towards the kidney allograft, because of shared HLA epitope mismatches between the kidney and MSC donor. In this study, we performed in-depth analysis of two cohorts (n=20) that received third-party MSC therapy after kidney transplantation. While the Neptune Study from Leiden University Medical Center specifically selected MSC to avoid repeated HLA antigen mismatches between kidney and MSC donors, the study from the University of Liège did not perform specific MSC selection. The comparative analysis of amino acid mismatches between these cohorts showed that selection of MSC to avoid repeated HLA mismatches at the split antigen level is not sufficient to prevent repeated mismatches at the amino acid level. However, repeated amino acid mismatches were not associated with the occurrence of donor-specific antibodies (DSA). The clinical relevance of repeated amino acid mismatches seems therefore limited for the risk of DSA formation. Since DSA formation in this study was limited (3 of 20 patients), larger studies are required to confirm that it is not necessary to prevent repeated HLA mismatches in allogeneic MSC therapy in kidney transplantation.